Experimental Investigation on the Influence of Regional Concrete Spalling on Shield Tunnel Segments - Shimin Wang; Chuankun Liu; Gaoyu Ma; Songyu Cao; Junbo Zhang; Daiyue Lu; Chuan He (Advances in Civil Engineering)
Based on the field investigation and analysis, the mechanical characteristics of segment structure in shield tunnels are compared and analyzed under the circumstances of different concrete spalling region by the method of similarity model experiment. Through data analysis of acoustic emission, the results for displacement and internal force of shield tunnel segments are clarified on the segment lining, the influential rule of load bearing capacity is also determined, and the deformation and stress for the different concrete spalling region are described as well. The corresponding research results indicate that range for elastic bearing stage is enlarged while it is narrowed for plastic bearing stage, the convergence and deformation and the accumulated event numbers for acoustic emission on critical instability point are obviously increasing, and the process of damage and failure tends to be sudden for segment lining structure. The ultimate bearing capacity of the damaged segment lining obviously decreases due to regional concrete spalling; to be more specific, the reduction rate for ultimate bearing capacity becomes 6%, 6%, and 13%, respectively, when the range of concrete spalling reaches 45°, 60°, and 75°.